Extraction of Natural Resources and Community Livelihoods Systems Change Region of the Cycloop Nature Reserve in Jayapura Papua - Novan Ngutra, Risky; Kumala Putri, Eka Intan; Hadi Dharmawan,, Arya; Darusman, Dudung (Sodality: Jurnal Sosiologi Pedesaan, 2017)
ABSTRACTThis study aims to analyze the pattern of community life of the Cycloop Nature Reserve based livelihoods.In  addition, this  study also analyzes the perception  of  the issues contained in the Cycloop  Mountains, nature  reserve, and analyze the management policy Cycloop Nature Reserve area. The results of the study noted that the pattern of use of forest resources  in  Cycloop Nature Reserve area in the form of social interaction of economic relations of society to meet the needs of everyday life, such as harvest forest products such as food, firewood, building materials and home, fodder, medicinal plantsand services and the results of other forest types. Perception noted there are four the most frequently encountered problems and facing communities, namely floods, forest fires and land (agriculture and illegal plantations), logging (illegal logging), as well as a decrease in the value of biodiversity in the area Cycloop Nature Reserve. The policy needs to be taken is the need for the empowerment of indigenous peoples through indigenous knowledge on the management of natural resources in the nature reserve. Additionally still conducted socialization activities for the community, then the pattern of routine patrols and security operations with indigenous peoples.Affirmation for customary land which is in the nature reserve area Cycloop Nature Reserveso that each of indigenous peoples supervise the activities of the society.Keywords: community interaction, perception, empowerment, indigenous knowledgeABSTRAKPenelitian ini bertujuan menganalisis aktivitas kehidupan masyarakat di kawasan Cagar Alam Pegunungan Cycloop berdasarkan mata pencaharian. Selain itu penelitian ini juga menganalisis persepsi mengenaiberbagai permasalahan di kawasan Cagar Alam Pegunungan Cycloop dan menganalisis kebijakan pengelolaan kawasan Cagar Alam Pegunungan Cycloop.Metode yang digunakan pada penelitian ini menggunakan analisis deskriptif dan analisis SWOT yang mengarahkan untuk kebijakan pengelolaan kawasan cagar alam. Hasil penelitian mencatat bahwa pola pemanfaatan sumberdaya hasil hutan pada kawasan Pegunungan Cycloops berupa hubungan interaksi sosial ekonomi masyarakat untuk memenuhi kebutuhan hidup sehari-hari, seperti kegiatan pemungutan hasil hutan berupa bahan pangan, kayu bakar, bahan rumah dan bangunan, pakan ternak, tanaman obat dan hasil jenis jasa hutan lainnya. Persepsi mencatat ada empat persoalan yang paling sering dijumpai dan dihadapi masyarakat, yakni banjir, kebakaran hutan dan lahan (pertanian dan perkebunan ilegal), pencurian kayu (illegal logging), serta penurunan nilai keanekaragaman hayati di kawasan Cagar Alam Pegunungan Cycloop. Kebijakan yang perlu diambil adalah perlu adanya pemberdayaan masyarakat adat melalui pengetahuan adat tentang pengelolaan sumberdaya alam di kawasan cagar alam. Selain itu tetap dilakukan kegiatan sosialisasi bagi masyarakat, kemudian pola pengamanan patroli rutin dan operasi secara bersama masyarakat adat. Penegasan bagi tanah adat yang berada di kawasan cagar alam Pegunungan Cycloops sehingga setiap masyarakat adat tetap mengawasi kegiatan masyarakatnya.Kata kunci: interaksi komunitas, persepsi, pemberdyaan, kearifan lokal